428. CHARACTERIZATION OF CD82/KAI1 IN ESOPHAGEAL ADENOCARCINOMA. (24th September 2022) - Ludwig, Alexandra; Limberger, Beate; Nowotny, Robert; Gockel, Ines; Thieme, René
Abstract: The incidence of esophageal adencocarcinoma (EAC) has increased in last decades. Regardless to improved perioperative chemotherapies and surgical approaches, the prognosis for EAC in advanced stages is poor. CD82 is a tumor suppressor gene, and its downregulation correlates with invasive growth, metastases formation and advanced clinical stages. CD82 might influence the Wnt/ß-catenin signaling pathway. We used an in vitro Barrett's esophagus cell culture model, represented by esophageal squamous cell epithelium (EPC1, EPC2), metaplasia (CP-A), dysplasia (CP-B) and esophageal adenocarcinoma (OE33, OE19, SKGT4, FLO1). Antisense LNA Oligonucleotides (GapmeRs, Qiagen) were used to achieve a transient knockdown of CD82 in OE33 and OE19 cells. mRNA and proteins were analyzed by q-RT-PCR and western blot analyses, respectively. A fluorescence antibody specific to CD82 was used for flow cytometry analysis. Proliferation assay, colony formation assay and boyden chamber assay were performed after CD82-knockdown to further analyze cell proliferation, cell growth and survival, colony forming and cell migration. CD82 was expressed in all investigated cell lines by flow cytometry with a significant overexpression in OE19 and FLO1 cells. A stable downregulation of CD82 was achieved in OE33 and OE19 cells. Proliferation assays showed a significantly higher proliferation rate at 72 hours after CD82-knockdown in OE33 cells. A significantly higher mRNA expression of vimentin was observed after CD82-knockdown in OE33. Colony formation assay showed a significantly higher colony count after CD82-knockdown in both cell lines. Cell migration was increased after CD82-downregulated in OE33 and OE19 cells. CD82 might influence the expression of mesenchymal marker proteins, cell migration abilities and the process of colony forming and thus enhance the metastatic potential of OE33 and OE19 cells. Low expression of CD82 could alter metastasis and cancer progression but further molecular characterizations are needed to elucidate the impact on carcinogenesis of EAC.